Determinants of Banking Habit of Urban People: A Study of Narayan Nagarpalika, Dailekh - Gautam, Ramesh Prasad (KMC Journal, 2024)
The banking industry has grown tremendously in volume and complexity in the last few decades. The banking habit rate in a country is an important indicator of growth in the economy. The purpose of this study is to find out the determinants of the banking habits of urban people. The study was conducted in Narayan Municipality, Dailekh. The data have been collected through a well-structured questionnaire from customers of different banks in the private and government sector. I selected a sample of 177 respondents from the population for the collection of data and to check the response of different customers. Descriptive and regression are utilized to see the cause-and-effect behaviour. The findings of the study indicate that availability and security play a significant role in the banking habit of urban people. This may help to identify the bottlenecks in the effective banking practices deployment in the urban areas.